2003
DOI: 10.1086/378623
|View full text |Cite
|
Sign up to set email alerts
|

Photon Orbital Angular Momentum in Astrophysics

Abstract: Astronomical observations of the orbital angular momentum of photons, a property of electromagnetic radiation that has come to the fore in recent years, have apparently never been attempted. Here I show how measurements of this property of photons have a number of astrophysical applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
165
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(168 citation statements)
references
References 22 publications
1
165
0
2
Order By: Relevance
“…The method has a limitation due to the overlap of the spots for different states that could be reduced by applying an additional diffraction grating to the first surface. The system opens the way to many interesting investigations ranging from experiments in multiport quantum entanglement [7], to applications in astrophysics [24] and microscopy [25], all of which make use of the OAM state basis.…”
mentioning
confidence: 99%
“…The method has a limitation due to the overlap of the spots for different states that could be reduced by applying an additional diffraction grating to the first surface. The system opens the way to many interesting investigations ranging from experiments in multiport quantum entanglement [7], to applications in astrophysics [24] and microscopy [25], all of which make use of the OAM state basis.…”
mentioning
confidence: 99%
“…In [10][11][12][13] it is implied that light is an electromagnetic wave. It carries electric and magnetic fields.…”
Section: Velocity and System Of Photonmentioning
confidence: 99%
“…Photonic orbital angular momentum (POAM), the fifth property of light, may be of significant interest to the astronomical community (Harwit 2003;Elias 2008). Since the discovery by Allen et al (1992) that POAM can be easily created in the laboratory, it has been found in virtually every field of optics Yao & Padgett (2011);Tamburini et al (2012); Shalaev et al (2013); Kim et al (2013); Chen et al (2013) ;Cristi & Axtell (2013); Sun et al (2013); Ruane & Swatzlander (2013); Roux (2013); this ubiquity is evident in the more than 1000 papers citing the original work (Allen et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several other methods have been developed to generate POAM in the laboratory (Oemrawsingh et al 2004;Gibson et al 2004;Gruneisen et al 2008). LaguerreGaussian beams are known as optical vortex beams because of their phase structure which is proportional to e ımφ , using the azimuthal angle, φ, and the OAM index, m. All of the photons in these optical vortex beams carry m of OAM (Harwit 2003). Identifying the states from such beams however, can be problematic and several different types of OAM sorters have been developed (Gruneisen et al 2008;Lavery et al 2011a,b;Sponselli & Lavery 2013).…”
Section: Introductionmentioning
confidence: 99%